2002
DOI: 10.3732/ajb.89.9.1373
|View full text |Cite
|
Sign up to set email alerts
|

Subdioecy in Consolea spinosissima (Cactaceae): breeding system and embryological studies

Abstract: The breeding system and the embryology of Consolea spinosissima, a tree-like opuntioid endemic to Jamaica, were investigated. Morphological and embryological studies revealed that the species is subdioecious, with three sexual morphs present in the 150 × 120 m plot studied at Hellshire Hills, Jamaica. The female morph has pistillate flowers with open stigma lobes, no pollen grains, and sets fruit. The male morph has cryptic staminate flowers with closed stigma lobes, viable pollen grains, and a nonfunctional g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
2
36
0
1
Order By: Relevance
“…Pistacia vera L. staminate flower; Hormaza & Polito, 1996). On the other hand, developmental inhibition would leave behind a more or less atrophied organ such as shriveled anthers with no pollen grains (Chaudhury et al 1994;Strittmatter et al 2002), anthers with non-functional pollen grains (Anderson & Symon, 1989;Caporali et al 2003), or indehiscent anthers (Arabidopsis msH mutant; Dawson et al 1992). According to Wu and Cheung (2000), programmed cell death (PCD) may be involved in either or both pathways.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Pistacia vera L. staminate flower; Hormaza & Polito, 1996). On the other hand, developmental inhibition would leave behind a more or less atrophied organ such as shriveled anthers with no pollen grains (Chaudhury et al 1994;Strittmatter et al 2002), anthers with non-functional pollen grains (Anderson & Symon, 1989;Caporali et al 2003), or indehiscent anthers (Arabidopsis msH mutant; Dawson et al 1992). According to Wu and Cheung (2000), programmed cell death (PCD) may be involved in either or both pathways.…”
mentioning
confidence: 99%
“…In this paper we focus on male sterility and its role in sex determination in a cryptically dioecious/subdioecious breeding system. The Caribbean endemic Consolea (Opuntioideae, Cactaceae) has nine species (Areces-Mallea, 2001), the six accessible species were studied and found to be subdioecious/cryptically dioecious (C. spinosissima - Strittmatter et al 2002;C. corallicola -Negrón-Ortiz & Strittmatter, 2004; all the other speciesunpubl.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers with non-functional organs of the opposite sex have been recorded both in trioecious and subdioecious species (Fleming et al, 1994;Strittmatter et al, 2002). Strittmatter et al (2002) reported that the non-functional anthers in pistillate flowers could have been maintained because they are adaptive, i.e., they mimic the appearance of the anthers of the male and hermaphrodite types, aiding in pollinator attraction. It is possible that the resemblance of the different flower types of C. cereifera could also represent a case of self-mimicry.…”
Section: Resultsmentioning
confidence: 99%
“…In the Cactaceae family, to date, there are 26 reported species, distributed among three of the four subfamilies, which develop unisexual flowers (Table S1). Most of these show non-functional vestiges of the opposite sex at anthesis (Lindsay and Dawson 1952;Bravo-Hollis 1978;Kimnach 1982;Leuenberger 1986;Del Castillo and González 1988;Hoffman 1992;Fleming et al 1994;ValienteBanuet et al 1997;Strittmatter et al 2002). The study of the mechanisms involved in unisexuality in Cactaceae species is an attractive model system because early evolutionary stages of the unisexuality process can be observed, probably due to the relatively recent origin of this family (Hershkovitz and Zimmer 1997;Nyffeler 2002;Edwards et al 2005).…”
Section: Introductionmentioning
confidence: 97%